Antibodies to K-α 1 tubulin and collagen V are associated with chronic rejection after lung transplantation - Hachem, R. R. (2012)
Bronchiolitis obliterans syndrome (BOS), the clinical correlate of chronic rejection after lung transplantation, is the leading obstacle to better long-term outcomes. We previously instituted a clinical protocol to screen for donor-specific human leukocyte antigen (HLA) antibodies (DSA) and a preemptive antibody-directed therapy protocol consisting of rituximab and/or intravenous immune globulin. In this study, we retrospectively analyzed serum samples from lung transplant recipients (n = 108) for antibodies to self-antigens (K-α 1 tubulin and collagen V) before and after antibody-directed therapy and correlated the results with the subsequent development of BOS. Seventy-two of the 108 recipients developed antibodies to self-antigens. There was a correlation between the development of antibodies to self-antigens and DSA. Sixteen of the 54 patients who had antibodies to self-antigens and were treated with antibody-directed therapy cleared the antibodies, and they were significantly less likely to develop BOS than those who had persistent antibodies. Furthermore, those who cleared DSA after treatment but had persistent antibodies to self-antigens were significantly more likely to develop BOS than those who cleared these antibodies. We conclude that antibodies to self-antigens are an important risk factor for the development of BOS.